Effect of Electrode Properties on the Performance of a Photosynthetic Microbial Fuel Cell for Atrazine Detection - Gonzalez Olias, Lola; Cameron, Petra J.; Di Lorenzo, Mirella (Frontiers in Energy Research, 2019)
The growing use of herbicides in agriculture poses increasing concerns on the pollution of water systems worldwide. To be able to assess the presence of these compounds in waters and limit their impact on human health and ecosystems, the development of effective in-situ monitoring tools is key. Yet, many existing sensing technologies are not suitable for in-situ and remote applications, due to challenges in portability, durability, cost and power requirements. In this study, we explore for the first time the use of an algal-assisted cathode in a photosynthetic microbial fuel cell (p-MFC) as a self-powered dissolved oxygen probe for herbicides detection in water. The cathode is enriched with the alga Scenedesmus obliquus and two different electrode materials are tested, graphite felt and indium tin oxide, which mainly differ in porosity, surface roughness and transparency. Despite the much larger specific surface area of graphite felt compared to indium tin oxide, the current generated under light was only 10 times larger (109 ± 2µA vs. 10.5 ± 0.6 µA) and 8 times larger in the dark (37 ± 5 µA vs. 4.2 ± 0.6 µA). By generating a current output that correlates with the dissolved oxygen in the catholyte, the resulting p-MFCs could detect the EU legal atrazine concentration limit of 0.1 µg L-1. The use of graphite felt led to shorter response times and better sensitivity, as a result of the greater current baseline. In both cases, the current baseline was recovered after exposure of the sensor to frequent toxic events, thus showing the resilience of the cathodic biofilm and the potential of the p-MFCs for early warnings of herbicides pollution in water.